HUBUNGAN FAKTOR PENGETAHUAN DENGAN TINGKAT KEPATUHAN MINUM OBAT ANTIHIPERTENSI (Studi Pada Pasien Hipertensi Essential di Wilayah Kerja Puskesmas Bandarharjo Kota Semarang) - Realita Nurhanani; Henry Setyawan Susanto; Ari Udiyono (Jurnal Kesehatan Masyarakat (Undip), 2020)
Compliance is the patient's behavior by following the doctor's advice in carrying out the therapy process. In 2017, the Bandarharjo Public Health Center is highest number of cases of hypertension were 7.935 cases with 28% treatment coverage. It has not known for certain the individual and social factors which are the main predictors of the low coverage of treatment at the Bandarharjo Health Center so that research needs to be done. The purpose of this study is to analyze the factors associated with the level of adherence to take antihypertensive drug in patients with essential hypertension in the working area of the Bandarharjo Public Health Center in Semarang. The method used in this research is a quantitative method with cross sectional study design with 148 research subjects. Bivariate results using chi-square test with a significance level of 5% stated age (p= 0.007), employment status (p= 0.040), level of knowledge of taking antihypertensive drug (p value= 0.001), level of health workers support (p= 0,000) associated to the level of adherence to take antihypertensive drug. It was concluded that age, occupational status, level of knowledge to take antihypertensive drug, level of health workers support, and hypertension control practices were related to levels of adherence to take antihypertensive drug. Advise given are to health workers to modify information provided to patients, other researchers to measure more deeply the other factors that shape respondents' perceptions of antihypertensive drug consumption.